2014
DOI: 10.1177/1098612x14551588
|View full text |Cite
|
Sign up to set email alerts
|

Gait and jump analysis in healthy cats using a pressure mat system

Abstract: Physical orthopaedic examination in cats does not always reveal signs of lameness and no objective gait analysis method has yet been standardised for use in cats. The aims of the present study were to define appropriate parameters for pressure mat analyses during walk and jump, and to define reference values for gait parameters of healthy cats. Further, the distribution of the vertical force within the paws and the influence of a non-centred head position were investigated. The hypothesis was that cats have a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
45
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(52 citation statements)
references
References 48 publications
6
45
1
Order By: Relevance
“…This achievement was likely reliant on the fact that we only included cats walking in a straight line without instances of pausing or trotting. Moreover, we had also excluded measurements taken when a cat turned their head during the recorded gait cycle, in consideration of the data reported by Stadig and Bergh [16] which showed an increase in PFz of the fore limbs related to the side that the head was positioned towards.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This achievement was likely reliant on the fact that we only included cats walking in a straight line without instances of pausing or trotting. Moreover, we had also excluded measurements taken when a cat turned their head during the recorded gait cycle, in consideration of the data reported by Stadig and Bergh [16] which showed an increase in PFz of the fore limbs related to the side that the head was positioned towards.…”
Section: Discussionmentioning
confidence: 99%
“…The investigations using PSWs have shown PFz for the forelimbs as ranging between 48.2% and 62.0% Bodymass (BM) [1115] and for the hind limbs as ranging between 38.3% and 50.2% BM [11, 13, 15], and IFz for the fore limbs as ranging between 12.7% and 18.9% BM [1115] and for the hind limbs as ranging between 13.1% and 14.6% BM [11, 13, 15]. Moreover, in the study of distribution of vertical force within feline paws, Stadig and Bergh [16] showed that the mean weight during a strike is transferred from the caudal towards the craniomedial part of the paw.…”
Section: Introductionmentioning
confidence: 99%
“…However, although several reports have evaluated gait symmetry and limb loading in cats, some of them have accepted the data generated even if a limb only contacted the walkway once or twice [26, 28] and wide ranges of velocity are accepted [19]. The present study highlighted the difficulty in collecting walking data from freely moving cats as velocity cannot be easily controlled, and in some cases, cats in the saline treatment group refused to walk.…”
Section: Discussionmentioning
confidence: 87%
“…One objective method to evaluate pain is gait analysis, which is only relevant if the origin of the pain affects gait. Pressure sensing platforms, or pressure sensitive walkways (PSW) have been investigated for the measurement of limb use in cats [19, 20] and used for the evaluation of limb use following onychectomy [21]. It is difficult to collect high quality limb use data when relying solely on cats freely walking across a PSW in a straight line (unpublished observations).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation